Acetylene sensor based on Pt/ZnO thick films as prepared by flame spray pyrolysis - Nittaya Tamaekong (2018)
ZnO nanoparticles loaded with 0.2-2.0 at.% Pt have been successfully produced in a single step by flame spray pyrolysis (FSP) technique using zinc naphthenate and platinum(II) acetylacetonate, as precursors dissolved in xylene and their acetylene sensing characteristics have been investigated. The particle properties were analyzed by XRD, BET, TEM, SEM and EDS. Under the 5/5 (precursor/oxygen) flame condition, ZnO nanoparticles and nanorods were observed. The crystallite sizes of ZnO spherical and hexagonal particles were found to be ranging from 5 to 20 nm while ZnO nanorods were seen to be 5-20 nm in width and 20-40 nm in length. In addition, very fine Pt nanoparticles with diameter of ∼1 nm were uniformly deposited on the surface of ZnO particles. From gas-sensing characterization, acetylene sensing characteristics of ZnO nanoparticles is significantly improved as Pt content increased from 0 to 2 at.%. The 2 at.% Pt loaded ZnO sensing film showed an optimum C2H2response of ∼836 at 1% acetylene concentration and 300 °C operating temperature. A low detection limit of 50 ppm was obtained at 300 °C operating temperature. In addition, Pt loaded ZnO sensing films exhibited good selectivity towards hydrogen, methane and carbon monoxide. © 2010 Elsevier B.V. All rights reserved.